attitudes of teachers regarding philosophy with or for children - miguélez vila, maría; raposo rivas, manuela (childhood & philosophy, 2024)
The philosophy program with and for children ‘FiloHilo’ arose from the possibility of transferring the innovative and renewed pedagogical processes based on philosophical dialogue and practice from the Practicum into the classroom. There are many studies that allow us to affirm that philosophy for children has become an effective, possible and necessary activity for all ages, as it responds to the needs of human beings: questioning, doubt. But these processes are established if there is an attitude of openness and willingness from teachers: this first condition, the attitude of openness and willingness, is the focus of this article and was the germ of key questions: How do teachers perceive these practices? Do they know about them? Have they used them at all in the past? Do they have a predisposition to their implementation? Are they prepared to develop ethical, reflexive, supportive and critical thought in their classrooms? With the goal of responding to these questions, we created a survey composed of 31 items and 4 dimensions that have high confidence levels (α=0.949). The survey was sent to all of the Galician educational centers and received responses from 167 teachers. The results showed a high predisposition towards philosophical practice fundamental supporting critical reasoning and awareness. Its conclusion demands a different approach to teaching philosophy, taking into account the needs and interests of philosophy teachers and introducing the need for training in the field of philosophical practice, understanding philosophy as practical and something that can change the lives of students: through self-knowledge and self-realization.